Dynamic Response Analysis of Medium-Speed Maglev Train with Track Random Irregularities - Peichang Yu (Hindawi-Wiley, 2021)
In order to analyze the dynamic response of medium-speed maglev train in the speed range of 0–200 km/h, the suspension performance, suspended energy consumption, and riding comfort of the train stimulated by random track irregularities are discussed in this paper. Firstly, the model of medium-speed maglev train including car body, air spring vibration isolation system, and the suspension system is established. Then, a controller based on flux inner feedback loop and PID outer feedback loop is designed for the suspension system. The established model is stimulated by the actual track power spectrum in full speed range. The simulation results show that the fluctuation of suspension gap is less than ±4 mm. Furthermore, thanks to the adding of permanent magnet, the power consumption is significantly reduced, which is of benefit to the electromagnet heating problem and on-board levitation power supply system. The riding comfort of the train moving on the irregular track using Sperling index is assessed. The experimental results validate the effectiveness of the proposed analytical calculation model of medium-speed maglev train. It is shown that medium-speed maglev train achieved good performance, significant power reduction, and satisfactory riding comfort.